The first case of Janibacter hoylei bacteremia in an adult. (2021) - Moktan, Varun; Elwasila, Sammer; Umadat, Goyal; Hata, D. Jane; Meza, Diana; Patel, Robin; Libertin, Claudia; Brumble, Lisa
Abstract: The Janibacter species are Gram positive, coryneform bacteria that belong to the Actinobacteria phylum and have been linked to bacteremia in immunocompromised children. We present the first documented adult case of Janibacter hoylei bacteremia. The patient was a 52-year-old woman with a history of recurrent Clostridioides difficile infection, sinus tachycardia and high-risk AML who had been admitted one month prior to presentation for matched unrelated donor hematopoietic stem cell transplant with reduced intensity fludarabine-melphalan. Thirty days post-transplant, the infectious disease team was consulted because blood cultures grew Janibacter hoylei, from one of two blood cultures It took nine days to identify the species. She was treated with linezolid and imipenem. Janibacter are rarely implicated in human pathology, and therein, usually identified in the context of malignancy and relative immunosuppression. J. hoylei was only previously reported from the bloodstream of a previously healthy 8-week-old infant without underlying medical conditions. Antimicrobial susceptibility testing is challenging as only in vitro susceptibility testing of Janibacter terrae has been reported. Given these challenges, it is our hope to illustrate the clinical approach to diagnosis as well as subsequent recommendations for treatment in a particularly challenging case of bacteremia in an AML patient.